1999
DOI: 10.1073/pnas.96.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocysterol [(24 Z )-ethylidenelanost-8-en-3β-ol], a rare sterol detected in the opportunistic pathogen Pneumocystis carinii hominis : Structural identity and chemical synthesis

Abstract: Pneumocysterol [(24Z)-ethylidenelanost-8-en-3␤-ol], a rare sterol detected in the opportunistic pathogenCommunicated by William Trager, The Rockefeller University, New York, NY, November 2, 1998 (received for review February 4, 1998 ABSTRACTPneumocystis carinii pneumonia (PcP) remains among the most prevalent opportunistic infections among AIDS patients. Currently, drugs used clinically for deep mycosis act by binding ergosterol or disrupting its biosynthesis. Although classified as a fungus, P. carinii lacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 30 publications
7
34
0
Order By: Relevance
“…These two compounds were identified in the present study of rat-derived P. carinii sterols. We here correct the trivial name (eburicol) for 24-methylenelanost-8-en-3␤-ol, which was incorrectly referred to as euphorbol in a previous report on P. jiroveci lanosterol derivatives (20). In the present study the definitive structure of 24-methylenelanosterol in P. carinii was confirmed.…”
Section: -En-3␤-ol (Lathosterol) N: Ergosta-724(28)-dien-3␤-ol (24-supporting
confidence: 71%
See 2 more Smart Citations
“…These two compounds were identified in the present study of rat-derived P. carinii sterols. We here correct the trivial name (eburicol) for 24-methylenelanost-8-en-3␤-ol, which was incorrectly referred to as euphorbol in a previous report on P. jiroveci lanosterol derivatives (20). In the present study the definitive structure of 24-methylenelanosterol in P. carinii was confirmed.…”
Section: -En-3␤-ol (Lathosterol) N: Ergosta-724(28)-dien-3␤-ol (24-supporting
confidence: 71%
“…This was later given the trivial name pneumocysterol when it was found to comprise a major component of some humanderived P. jiroveci (P. carinii f. sp. hominis) isolated organism populations (20). Pneumocysterol and 24-methylenelanosterol have now been definitively identified in ratderived P. carinii (P. carinii f. sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-24 of lanosterol is a major site of sterol metabolism in plants, fungi, and animals [1,2,3]. As a result of our continuing studies on sterol biosynthesis, we have devised a simplified chemical synthesis of 3β-acetoxy-lanost-8-en-24-one (2, 24-ketolanosteryl acetate), a key intermediate in the synthesis of C-24 alkylated metabolites and potential regulators of sterol biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography data are available for characterization of P. jirovecii with low C 31 and C 32 sterols (Kaneshiro et al, 1999a) but definitive structural assignments by mass spectrometry and nuclear magnetic resonance spectroscopy have yet to be reported. in P. jirovecii populations with high C 31 and C 32 sterols, the lanosterol derivative pneumocysterol (Kaneshiro et al, 1999b) (24Z)-ethylidenelanost-8-en-3b-ol can accumulate often comprising about half the Pneumocystisspecific sterols. Definitive structural analyses of sterols in a population with high C 31 and C 32 sterols indicated that those P. jirovecii organisms lacked 14DM activity (14DM -) (Giner et al, 2004).…”
Section: Recombinant Pneumocystis Sterol Biosynthesis Enzymesmentioning
confidence: 99%